Edición génica en inoculantes de soja por CRISPR-Cas9 : Mejoramientos para una mayor sostenibilidad agrícola - Serantes, María Laura; Stritzler, Margarita; Brambilla, Silvina Maricel; Ayub, Nicolás Daniel (INTA, 2025)
Poster